Endometrial scratching in unexplained repeated implantation failure causes two competing forces, angiogenesis and anti-angiogenesis: An RCT study - Samaneh Aghajanpour; Fereshteh Mehraein; Fatemehsadat Amjadi; Zahra Zandieh; Firouzeh Ghaffari; Khashayar Aflatoonian; Elham Hosseini; Mehrdad Bakhtiyari; Reza Aflatoonian (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: A significant association between endometrial vascularity and pregnancy has been shown in previous research, while poor vascularization was attributed to repeated implantation failure (RIF). One possible approach to enhance angiogenesis for successful implantation is endometrial scratching (ES). Objective: The purpose was to investigate endometrial responses to scratching by profiling angiogenesis-related gene expression in unexplained RIF participants. Materials and Methods: In this randomized controlled trial study, 20 infertile women with unexplained RIF were assigned to 2 groups by the balanced block randomization method (n = 10/each group): the intervention group (group A) (who received ES in the follicular phase) and the control group (group B). Endometrial biopsy was performed in the secretory phase. Gene expression profiling was performed using a polymerase chain reaction-array kit for human-angiogenic growth factors. The implantation and clinical pregnancy rates were also assessed. Results: Among the angiogenesis-promoting genes, FGF1, FGF13, FGF2, TGFA, ANG, ANGPT1, and VEGFA were significantly upregulated (p < 0.05). IL12A (an angiogenesis-inhibiting cytokine) was significantly upregulated (p < 0.01). In contrast, 15 genes with angiogenesis-related functions, including CXCL11, CXCL13, CXCL3, CXCL5, CXCL6, EREG, FIGF, FST, IL10, LEP, PPBP, PROK1, RHOB, TNF, and TYMP, were downregulated after ES. No significant differences were observed between the intervention (group A) and control (group B) groups in terms of implantation (43.75% vs. 28.57%) or clinical pregnancy rates (75% vs. 57.1%). Conclusion: ES induced significant alterations in the expression of angiogenesis-related genes, with notable up/downregulation of key angiogenic/antiangiogenic factors. These findings enhance our understanding of the molecular responses triggered by ES, underscoring the potential influence of ES on the complex processes of angiogenesis crucial for implantation.